Math, asked by pregatiaggarwal123, 1 year ago

Find the general solution of the following equation....
cot^{2}Ф +\frac{3}{sinФ}  +3=0

Answers

Answered by BrainlyPopularman
8

Question :

▪︎ Find the general solution of the following equation –

 \\ \implies { \bold{cot^{2} \phi +\dfrac{3}{sin \phi} +3=0}} \\

ANSWER :

 \\ \implies { \bold{cot^{2} \phi +\dfrac{3}{sin \phi} +3=0}} \\

• We know that –

 \\ \implies { \red{ \boxed{ \bold{cot^{2} \phi  =  \frac{ {cos}^{2} \phi }{ {sin}^{2} \phi } }}}} \\

• So that –

 \\ \implies { \bold{ \dfrac{cos^{2} \phi}{ {sin}^{2}  \phi} +\dfrac{3}{sin \phi} +3=0}} \\

 \\ \implies { \bold{ cos^{2} \phi \: + 3 {sin}  \phi +3 {sin}^{2} \phi =0}} \\

• We should write this as –

 \\ \implies { \bold{ cos^{2} \phi \: +  {sin}^{2} \phi  + 3 \:  {sin}  \phi +2 {sin}^{2} \phi =0}} \\

• Let's use –

 \\ \implies { \red{ \boxed{ \bold{cos^{2} \phi  \:   +  {sin}^{2}  \phi=1 }}}} \\

 \\ \implies { \bold{ 1 + 3 \:  {sin}  \phi +2 {sin}^{2} \phi =0}} \\

 \\ \implies { \bold{ 2 {sin}^{2} \phi + 3 \:  {sin}  \phi  + 1 =0}} \\

 \\ \implies { \bold{ 2 {sin}^{2} \phi + 2 \:  {sin}  \phi   + sin \phi+ 1 =0}} \\

 \\ \implies { \bold{ 2 {sin} \phi ( \:  {sin}  \phi    + 1)+ 1(sin \phi+ 1) =0}} \\

 \\ \implies { \bold{( 2  \: {sin} \phi + 1) ( \:  {sin}  \phi    + 1)  =0}} \\

 \\ \implies { \bold{  {sin} \phi  =  -   \frac{1}{2}   \: , \:  {sin}  \phi     =  - 1  }} \\

▪︎ If   \: { \bold{sin \theta  =  {sin} \phi  }} \:  then general solution –

 \\ \implies { \red{ \boxed{ \bold{ \theta  = n \pi  +  {( - 1)}^{n}  }}}} \\

 \\  \:  \:  . \:  \: {  \pink{\bold{ \underline{  when \:  \: sin( \phi) =   -  \frac{1}{2}  } :  - }}} \\

 \\ \implies { \bold{  {sin} \phi  =  -   \frac{1}{2}  }} \\

 \\ \implies { \bold{  {sin} \phi  = - sin( \frac{ \pi}{6}  ) }} \\

 \\ \implies { \bold{  {sin} \phi  =  sin( \pi + \frac{ \pi}{6}  ) }} \\

 \\ \implies { \bold{  {sin} \phi  =  sin( \frac{ 7\pi}{6}  ) }} \\

 \\ \implies {\bold{   \phi  = n\pi + ( - 1) ^{n}( \frac{7\pi}{6})  \:  \:  \: [Genral \:  \: solution]}} \\

 \\  \:  \:  . \:  \: {  \pink{\bold{ \underline{  when \:  \: sin( \phi) =   -  1  } :  - }}} \\

 \\ \implies { \bold{  {sin} \phi  =  -  1  }} \\

 \\ \implies { \bold{  {sin} \phi  =  - sin( \frac{\pi}{2} ) }} \\

 \\ \implies { \bold{  {sin} \phi  =   sin( \pi + \frac{\pi}{2} ) }} \\

 \\ \implies { \bold{  {sin} \phi  =   sin( \frac{3\pi}{2} ) }} \\

 \\ \implies {\bold{   \phi  = n\pi + ( - 1) ^{n}( \frac{3\pi}{2})  \:  \:  \: [Genral \:  \: solution]}} \\

Similar questions